1230 Infrainguinal Bypass Informed Consent: An Audit Driven Standardisation Of Perioperative Risk Profiling. (12th October 2021) - Muhammad, K; Al-Khaffaf, H
Abstract: Introduction: It is a fundamental good clinical practice in our medicolegal rights era to obtain standard, adequate, and transparent informed consent before any planned intervention. Currently, there are neither national approved vascular intervention-specific consents nor explicit guidelines for it. We aim to achieve a standardisation of perioperative risk profiling of infrainguinal bypass surgical consents and produce a model one. Method: A retrospective analysis of 45 infrainguinal bypass consents (audit/reaudit) between (2013-2019) retrieved to evaluate quality and completeness against GMC 2008 guidance: "Consent: patients and doctors making decisions together". Data included basic consent requirements according to guidelines and speciﬁc risks of infrainguinal bypass. It was registered with the Trust Clinical Audit Department. Results: (100%) of audit and reaudit consents documented the intended benefits of surgery. Inclusion into the National Vascular Registry (NVR) was achieved (0%) in audit vs (80%) in reaudit forms. Of the 19 documented postoperative complications, reaudit significant improvement observed in % of documenting 16 items with 9 complications recorded above 50%. The maximum number of audit documented risks was 15 (79%), the median 8 (42%), and the least was 3 (16%) compared to maximum 16 (84%), the median 10 (53%) and the least was 4 (21%) when reaudited, respectively. Conclusions: Deficiencies in performing and adequately completing surgical consents still occur. Introducing a national pre-printed vascular intervention-specific consent is vital for accomplishing and maintaining a good clinical practice. It should include all complications with relative % risk to minimise errors, provide good quality consent, and promote clinical practice at a national level.